Corporate Risk as a Mediator in Banking Financial Performance: Examining the Impacts of Sustainable Finance, Governance, and Auditor Reputation - Azizah, Farah Nur; Lastanti, Hexana Sri (WIDYAKALA JOURNAL : JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2025)
This study investigates the role of corporate risk as a mediator in the relationship between sustainable finance, governance mechanisms, and auditor reputation on banking financial performance. With the increasing emphasis on sustainable finance, particularly following regulations like POJK No.51/POJK.03/2017, the integration of economic, social, and environmental factors in financial reporting has gained prominence. The research employs a quantitative methodology using SMARTPLS version 4.0 and SEM-PLS analysis, focusing on data from banking institutions listed on the Indonesia Stock Exchange from 2021 to 2023. The findings reveal that auditor reputation significantly enhances financial performance, while corporate risk negatively impacts it. Sustainable finance shows a positive but insignificant effect, and governance mechanisms do not significantly influence financial performance. Notably, corporate risk significantly mediates the relationship between sustainable finance and financial performance, indicating that effective risk management is crucial for leveraging sustainable finance initiatives. This study contributes to the understanding of how corporate governance and sustainable practices can enhance financial stability in the banking sector